ON THE CORRECTNESS OF DIFFERENTIAL AND DIFFERENCE METHODS FOR ANALYSIS OF THE STABILITY OF CONTINUOUS RAILWAYS - Smilijanow, Atanas; Mitrov, Zvetan (Ann. Sofia Univ. Fac. Math. and Inf., 1991)
The problem of the rail ways stability exists for a long time and there are about 100 theoretical methods to solve it. In this paper the connection between differential and difference methods is discussed.